Strategi Pengembangan Ekowisata Mangrove Muara Bengawan Solo di Desa Pangkah Wetan, Kecamatan Ujungpangkah, Kabupaten Gresik - Aminah Roisatul Kubro; Nur Ocvanny Amir (Universitas Muhammadiyah Malang, 2018)
Pangkah Wetan village has begun to utilize mangrove forests. At present, mangrove forests have been developed as ecotourism objects, however, the management has not developed them maximally. This study aims to determine the strengths, weaknesses, opportunities, and threats, as well as to analyze the strategies used in developing ecotourism at Muara Bengawan Solo Mangrove. Six key informants were selected as resource persons, while 30 respondents were selected by accidental sampling, they became the subject of analysis. The tool used is SWOT analysis (Strength, Weakness, Opportunity, Threat) and Quantitative Strategic Planning Matrix (QSPM). The results shows that the biggest score 1.84 was obtained at the opportunity, while the threat score was 0.84 so that this mangrove ecotourism still has many opportunities that could be used in developing ecotourism. The scores of strengths and weaknesses are 1.62 and 1.22, with a score difference of 0.4 only. The strength is only a slight difference from its weaknesses. Based on QSPM, an alternative strategy is obtained with the highest score of 5.71% at the first alternative. Application of the strategy used in developing mangrove ecotourism is the improvement of facilities provided to visitors.